Mandible reconstruction after head and neck management for oral cancer: A case report and literature review - Sylvio Luiz Costa De-Moraes; Raissa Dias Fares; Alexandre Maurity de Paula Afonso; Roberto Gomes dos Santos; Ricardo Pereira Mattos (Oral Oncology Reports)
The use of mandibular osteotomies to allow access to tumors of the oral cavity and oropharynx is common for head and neck surgeons. However, the nature and frequency of complications associated with this procedure vary in many articles. The purpose of this study is to present a case of floor-of-mouth squamous cell carcinoma in a female patient who underwent radiotherapy and chemotherapy for subsequent resection of the tumor with cervical dissection (level 1,2,3) as the first surgical act by head and neck surgeons. The patient developed malocclusion and halitosis which was treated as late radiation tissue injury with prescribed hyperbaric oxygen therapy (HBOT). Although the procedure related to cancer was successful the mandible reduction and fixation were not enough. For this reason, the patient needed a second surgery for the reconstruction of the mandible using vascularized bone with maxillofacial surgeons. The patient had a good evolution, the 5-year postoperative follow-up of complete surgical removal of the cancer and reconstruction proved to be a viable resource for improving the patient's quality of life.